(ARTICLE RETRACTED) Diagnostic value of VIA comparing with conventional Pap smear in the detection of colposcopic biopsy proved CIN - Hegde, D; Shetty, H; Shetty, PK; Rai, S; Manjeera, L; Vyas, N; Hegde, A; Mallya, H; Rajesh, A (Bangladesh Journal of Medical Science, 2011)
This article has been retracted because it has already been published in the Nepal Journal of Obstetrics and Gynaecology Vol.6(1) 2011 pp.7-12. http://www.nepjol.info/index.php/NJOG/article/view/5245